Peranan Magnetic Resonance Imaging (MRI) Lumbal dalam Penegakan Diagnosis Kasus Low Back Pain: Studi Kasus di Instalasi Radiologi Rumah Sakit Satya Negara Jakarta Utara - Wahyu Setiyoningsih; Nursama Heru Apriantoro (Poltekkes Kemenkes Semarang, 2023)
Background: Magnetic resonance imaging (MRI) is considered the best imaging for chronic low back pain because of high tissue contrast and no effect of ionizing radiation. The purpose of this study was to determine the management of Lumbar MRI examination with Low Back Pain Cases.Methods: The research used was a qualitative descriptive research method by collecting data by direct observation which was conducted in December 2022 at Satya Negara Hospital, North Jakarta. The research was conducted using direct observation methods, documentation and decision studies. The sample used was 1 patient.Results: The image results are strengthened by the expertise of a radiologist. The results of the study were obtained from the beginning of the patient's process of coming to radiology to perform a Lumbar MRI examination in the administration section until the examination was completed. Using a GE 1.5 T MRI machine and a whole spine coil. The sequences used are 3-plane location, calibration scan lumbar, Coronal T2, Sagittal T2, Sagittal T1, Sagittal T2 + FATSAT, Axial T2, Sagittal Myelography, Coronal Myelography.Conclusions: This study shows that Lumbar MRI image results and the doctor's expertise show that there is grade I spondylolithesis and L4-L5 spondyloarthrosis with disc protrusion. It’s mean that MRI can provide information for making a diagnosis.